MUTU PELAYANAN BIDAN PRAKTEK MANDIRI KOTA SURABAYA - Nuraini, Indria (Program Studi S1 Kebidanan - Fakultas Sains dan Kesehatan Universitas PGRI Adi Buana Surabaya, 2015)
Background: From year to year in the Independent Practice Midwife Surabaya City has experienced an increase in health care with the Bidan Delima. But all this is not enough if there are many important aspects that have not been improved, such as hospitality midwife and the midwife are less communicative with patients and tackle these and slow in decision making in emergencies. Objective: To determine the quality of health care in Independent Practice Midwife Surabaya City. Methods: The design used was descriptive qualitative with case study a stuck strategy. The subjects of this study were all Independent Practice Midwife in Surabaya and retrieved using purposive sampling technique. The process of data retrieval was done by in-depth interviews. Confidence data test consists of the credibility and transferability test, while the data analysis using inductive thinking process. Results: The quality of services provided by BPM has met the four dimensions of quality of service properly, that is reliability, responsiveness, empathy and assurance, while the tangible dimension still need improvement. Services in BPM is fast, precise and midwives are very friendly and very caring towards his clients. The entire informants were satisfied and midwife services are perceived better than hospital services. The hope from informant, BPM can improve support facilities such as parking and air conditioning. In addition to the equipment used by all midwives studied were standard and no modifications. Suggestion: For independently practice midwfeexpected to develop the quality of services, especially the provision of means of support so as to improve the competitiveness of BPM